2017
DOI: 10.1139/as-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of thermokarst lake water balance in high-latitude regions of North America from isotope tracers

Abstract: Numerous studies utilizing remote sensing imagery and other methods have documented that thermokarst lakes are undergoing varied hydrological transitions in response to recent climate changes, from surface area expansion to drainage and evaporative desiccation. Here, we provide a synthesis of hydrological conditions for 376 lakes of mainly thermokarst origin across high-latitude North America. We assemble surface water isotope compositions measured during the past decade at five lake-rich landscapes including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 70 publications
3
28
1
Order By: Relevance
“…by the strong influence of evaporation. This agrees with model predictions that lakes in the Mackenzie Delta, downstream of the PAD, will become increasingly sensitive to local climate conditions as frequency and magnitude of flooding decreases (Marsh and Lesack 1996). We suspect that cumulative effects of long-term and ongoing decline in frequency and magnitude of river flooding, and arid conditions, are the dominant influence on the hydrological and limnological trajectory of lakes in the PAD, which, apparently is now unlikely to be altered by a single and isolated large flood event.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…by the strong influence of evaporation. This agrees with model predictions that lakes in the Mackenzie Delta, downstream of the PAD, will become increasingly sensitive to local climate conditions as frequency and magnitude of flooding decreases (Marsh and Lesack 1996). We suspect that cumulative effects of long-term and ongoing decline in frequency and magnitude of river flooding, and arid conditions, are the dominant influence on the hydrological and limnological trajectory of lakes in the PAD, which, apparently is now unlikely to be altered by a single and isolated large flood event.…”
Section: Discussionsupporting
confidence: 87%
“…The 2000–2015 PAD isotope framework was then used to calculate evaporation to inflow ( E/I ) ratios, an index of lake‐water balance described by Gibson and Edwards () and others. As in many regional studies that have used this approach (e.g., Brooks et al ; Gibson et al ; MacDonald et al ), we compare E/I ratios across a large number of lakes to differentiate regions of the delta. E/I ratios were calculated as: EI=|δnormalIδnormalL|δnormalEδnormalL where δ E is the isotope composition of evaporative flux (Craig and Gordon 1965), δ L is the lake water isotope composition, and δ I is the isotope composition of input waters to the lake ( see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Continued climate warming and permafrost thawing will alter regional hydrologic systems and the spatial distribution of surface water resources, creating subsurface flow pathways . Previous studies have shown that permafrost degradation has significantly changed the water balance of thermokarst lakes, meltwater of ground ice contributes about one‐third of the input water to thermokarst lakes, and permafrost thaw controls changes of thermokarst lake status (number, size) and related hydrological variabilities …”
Section: Introductionmentioning
confidence: 99%
“…Due to the spatial heterogeneity of permafrost, vegetation cover and climate controls, the hydrological processes of thermokarst lakes were found to vary at each site . The distribution of permafrost also revealed different impacts on the initial source water . However, large‐scale investigations of the hydrology of thermokarst lakes on the QTP are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Once the water reaches the lake, however, evaporation from the lake surface causes enrichments of both deuterium and 18 O and displaces the lake isotopic compositions below the MWL (e.g., Craig 1961;Dinçer 1968;Gat et al 1994;Teranes and McKenzie 2001;Brock et al 2009;Turner et al 2010). Multiple lakes within a region characteristically define a line in dD vs. d 18 O space, which is referred to as the "local evaporation line" (e.g., Gibson 2001;Gibson and Edwards 2002;Gibson et al 2005;Henderson and Shuman 2009;Kebede et al 2009;MacDonald et al 2017). Figure 1 shows a typical local evaporation line (LEL), which intercepts with the LMWL at the depleted end, and extends upward with a positive dD-d 18 O slope less than 8.…”
mentioning
confidence: 99%